Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/er.5054
|View full text |Cite
|
Sign up to set email alerts
|

Development of the inorganic composite phase change materials for passive thermal management of Li‐ion batteries: material characterization

Abstract: Summary The battery thermal management system based on phase change materials (PCMs) has proven to be a safe, inexpensive, and high‐performance technology, which is currently gaining popularity over the other battery thermal management systems. PCMs are able to absorb heat generated by batteries, prolong battery life, and improve their performance. Organic compounds, such as paraffin, are widely used as phase change materials for the battery thermal management systems; however, there are no published data on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…All three PCMs were added with EG matrix to improve their thermal conductivity. It is revealed that both inorganic PCMs could be potential candidates for BTMS of LIB packs 98 . A composite matrix coupled with a mini‐channel‐based BTMS system is designed and studies the thermal performance at various discharge rates, air natural convection (ANC), and composite matrix (CM).…”
Section: Recent Work Related To Organic and Inorganic Pcms With Heat ...mentioning
confidence: 99%
“…All three PCMs were added with EG matrix to improve their thermal conductivity. It is revealed that both inorganic PCMs could be potential candidates for BTMS of LIB packs 98 . A composite matrix coupled with a mini‐channel‐based BTMS system is designed and studies the thermal performance at various discharge rates, air natural convection (ANC), and composite matrix (CM).…”
Section: Recent Work Related To Organic and Inorganic Pcms With Heat ...mentioning
confidence: 99%
“…These techniques enable rapid and accurate identification of the elemental and molecular components present in the batteries. 98 The physical characteristics of the battery, including its appearance, marking information, battery voltage, and weight, are examined. Additionally, chemical analysis techniques are employed to determine the chemical composition of the battery, such as the positive and negative electrode materials and electrolyte composition.…”
Section: Recycling Techniquesmentioning
confidence: 99%
“…Therefore, these devices urgently need micro energy or a power plant with high energy density, so that they can give full play to their advantages and further miniaturization and multifunction. However, the batteries commonly employed in micro electro mechanical systems have some problems, such as long charging times, large size, weight, and low energy density [7][8][9] . The MPGS is largely driven by the micro-combustion of hydrocarbon fuel in compact or restricted places, termed micro-combustors.…”
Section: Introductionmentioning
confidence: 99%